Multisensory Rehabilitation Training Improves Spatial Perception in Totally but Not Partially Visually Deprived Children - Cappagli, Giulia; Finocchietti, Sara; Baud-Bovy, Gabriel; Cocchi, Elena; Gori, Monica (Frontiers in Integrative Neuroscience, 2017)
Since it has been shown that spatial development can be delayed in blind children, focused sensorimotor trainings that associate auditory and motor information might be used to prevent the risk of spatial-related developmental delays or impairments from an early age. With this aim, we proposed a new technological device based on the implicit link between action and perception: ABBI (Audio Bracelet for Blind Interaction) is an audio bracelet that produces a sound when a movement occurs by allowing the substitution of the visuo-motor association with a new audio-motor association. In this study, we assessed the effects of an extensive but entertaining sensorimotor training with ABBI on the development of spatial hearing in a group of seven 3–5 years old children with congenital blindness (n = 2; light perception or no perception of light) or low vision (n = 5; visual acuity range 1.1–1.7 LogMAR). The training required the participants to play several spatial games individually and/or together with the rehabilitator one hour per week for three months: the spatial games consisted of exercises meant to train their ability to associate visual and motor-related signals from their body, in order to foster the development of multisensory processes. We measured spatial performance by asking participants to indicate the position of one single fixed (static condition) or moving (dynamic condition) sound source on a vertical sensorized surface. We found that spatial performance of congenitally blind but not low vision children is improved after the training, indicating that early interventions with the use of science-driven devices based on multisensory capabilities can provide consistent advancements in therapeutic interventions, improving the quality of life of children with visual disability.